Context-Sensitive Phonological Processes of Alveolar Liquid Consonants in Syllable-Final Position Within Letters in Neogranadian Spanish - Díaz Romero, Camilo Enrique (2024)
This article aims to show an approximation on diatopic and social variation from traces, originating from letters written during the Neogranadian colonial period, of context-sensitive phonological processes that affected alveolar liquid consonants in syllable-final position. Thus, methods with and without georeferencing are used, which allow us to make a general historical proposal about which sound substitutions were documented between 1550 and 1825. Testimonies of lateralizations and assimilations are regularly found throughout the period under review, the first having a considerable presence in women and the second, in educated users during the 17th century. Samples of vowel insertion are only found in the interior of colonial territory, while rhotacisms were reported in coastal areas.